FITOREMEDIASI Zn DARI LIMBAH CAIR PABRIK PENGOLAHAN KARET DENGAN PEMANFAATAN Pistia stratiotes L. - Ningsih, Indah Sri Rahma; Lestari, Wahyu; Azis, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Rubber processing factory is one of big industries in Riau and potentially produce heavy metal such as Zn. The continuous factory activity will produce high level of Zn in liquid waste and cause the contamination of aquatic environment.  One of the alternative efforts to overcome this effect is  using phytoremediation.  P. stratiotes  that is known as a plant that may accumulate metals (Pb, Cd, Cr and Zn)  at high concentration.  This research aimed to test the ability of the growth of  P. stratiotes  and the ability of  P. stratiotes in reducing the content of Zn in liquid waste of rubber processing factory. The research used Complete Random Design.  P. stratiotes  was grown for 20 days in liquid waste of rubber processing factory with the concentrations were 5, 10, 15, 20, 25% and without the liquid waste as a control (0%).  Each concentration had 3 replications. Parameters observed were fresh weight gain and relative growth rate of  P. stratiotes. Data was  analyzed using ANOVA and LSD at the level of 5%. The results showed that the fresh weight  P. stratiotes  increased up to 33.65 g in the concentration of 25%.  The highest relative growth was found in 5thday for all concentrations and control.